The relationship between cultural norms, interdependent self-construal, perceived cooperative communication, and interaction goals: A study of Malaysia-China international business negotiations - Soo, Hoo Pin Lick (2024)
Since diplomatic relations between Malaysia and China began in 1974, China has been a trading partner to Malaysia, and starting in 2008, Malaysia has become China’s main trading partner. In this regard, the business collaborations between Malaysia and China have increased, and thus, there will be more frequent communication between the two parties. It is through communication that the two parties build relationships to gain trust, understand each other’s needs, and reach mutual agreements. Therefore, the main aim of this study is to examine the relationship between cultural norms, interdependent self-construal, perceived cooperative communication, and interaction goals in the context of Malaysia-China international business negotiations. The GLOBE model is the main model used in this study. It is supported by two theories, which are face-negotiation theory and similarity-attraction theory. This study was conducted based on the GLOBE model’s nine cultural dimensions. Respondents of this study were Malaysian and Chinese businesspeople that involved in Malaysia-China international business negotiations. The results show that cultural norms, interdependent self-construal, and perceived cooperative communication lead to positive interaction goals (negotiation outcome), confirming the use of the GLOBE model, face-negotiation theory, and similarity-attraction theory that are being used to explain the findings. This study also shows interdependent self-construal mediates the relationship between cultural norms and interaction goals. The findings also reveal that perceived cooperative communication mediates the relationship between interdependent self-construal and interaction goals, highlighting the crucial role of perceived cooperative communication as an essential factor in achieving interaction goals and negotiation outcomes. The outcomes of this study contribute to having effective communication and negotiation between Malaysia and China on the global stage. The model of this study can be referred to as a guideline for business people who are interested in business ventures in Malaysia and China.